Characteristics of Trace Elements in Volcanic ash of Kelud Eruption in East Java, Indonesia - Diah Dwiana Lestiani; Revi Apryani; Linda Lestari; Muhayatun Santoso; Eko Prabowo Hadisantoso; Syukria Kurniawati (Indonesian Journal of Chemistry, 2018)
The eruption of Mount Kelud that occurred on February 13, 2014, ejected a huge plume of ash and sand exceeding 26 km into the air which moved west over the island. The elements content in volcanic ash is important information for further study such as the possibility to utilize the ash. In this study, the volcanic ashes collected from four affected areas in Java were analyzed using neutron activation analysis (NAA) with HPGe detector and X-ray fluorescence. Method validation was applied using the standard reference material SRM NIST 2711a Montana Soil with recovery and accuracy in a good agreement for all elements. The analysis results of volcanic ashes showed a wide range of elements, major elements Al, Ca, Fe, K, Mg, Mn, Na, Si and Ti, trace elements As, Cd, Cu, Co, Cr, V, Zn, Hf, Th and U, and rare earth elements were identified. The results showed heavy metals As, Cd, Cu, Co, Cr, and Pb were ranged 3.23–4.42, 17.63–24.09, 49.26–77.10, 10.86–16.03, 11.19–17.79 and 31.4–42.7 mg/kg, respectively, while rare earth elements such as Ce, Eu, La, and Sm were 9.84–18.43, 0.73–1.02, 2.25–5.66 and 1.34–2.63 mg/kg respectively. Comparison with other volcanic ashes from Indonesia such as Merapi and Sinabung and world volcanic ashes were applied. The results of the characteristic of elements in Kelud volcanic ash would be valuable information as reference data for their potential utilization.